Sosialisasi Kebijakan Lingkungan Hidup Kepada Masyarakat Desa Pisang Berebus Mewujudkan Good Governance - Muhammad Zuhidayat; Alnanda Satrio; Olivia Yolanda; Amelia Jelita Putri; Amanda Mardissi; Addina Fitria; Yadira Maharani; Dewi Angel Caroline; Nur Ramayanti; Phalosa Dwi Apsalina; Afdhalon Ikhsan (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Environmental cleanliness is the most important thing in achieving a healthy life. Activities are needed that encourage people to start living healthy lives. One of these activities is healthy environmental activities through real work college work programs. This activity aims to: 1) make the community aware of the benefits of clean living and its impact on health, 2) provide knowledge to the community about the negative impacts of an unclean and unsanitary environment, 3) help the community clean the environment around where they live through field action activities in the form of distributing rubbish bins, and mutual cooperation and also reforestation by planting trees. This community service activity is delivered using discussion, counseling and field action methods. Several things that need to be considered after this activity takes place are that activities like this should be carried out regularly every year because so far people have not paid attention to the cleanliness of their environment so they are prone to disease and natural disasters such as floods. After this activity was completed, the results were that so far people tend to ignore the cleanliness of their environment, so assistance from various parties is needed so that people care about the surrounding environment. They are also committed to protecting the environment where they live.